Effectiveness of disaster risk reduction management information dissemination before, during, and after typhoons - Karl Allen V. Aquino; Paolo Carl E. Soliven (Indonesian Journal of Social Sciences, 2026)
The City Disaster Risk Reduction and Management Office (CDRRMO) in the Philippines is mandated to disseminate information and communicate disaster risks to the public. This study aimed to evaluate the effectiveness of the CDRRMO's information dissemination efforts in the occurrence of a typhoon in a barangay in Science City of Muñoz, Nueva Ecija. Using a correlational research design, a survey was conducted with 93 residents to assess their level of awareness of information disseminated by the CDRRMO before, during, and after a typhoon. The results indicated that respondents' awareness of the CDRRMO's initiatives before, during, and after the typhoon was moderate. A significant finding showed that respondents showed a higher level of awareness regarding information disseminated after the typhoon compared to before and during the event. The study also found a correlation between the respondents' awareness and the CDRRMO's effectiveness in disseminating information. The study concluded that to improve public awareness and enhance communication, the CDRRMO should increase the use and distribution of accessible print materials, particularly at the barangay level. That highlights how effective communication is crucial for mitigating risks in the aftermath of a disaster, especially at the grassroots levels.